2018
DOI: 10.2478/jvetres-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of haematological and biochemical blood parameters after electrical cardioversion of atrial fibrillation in dogs

Abstract: Introduction: Electrical cardioversion is a therapeutic procedure used to convert various types of arrhythmias back to sinus rhythm. It is used to restore the sinus rhythm in dogs with atrial fibrillation. The effect of the electrical energy used during cardioversion on red blood cells (RBC) is not fully understood. Studies on humans reported lysis of RBC following electrical cardioversion. Similar studies have not been carried out on dogs. The aim of the study was to assess the effect of electrical cardiovers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Why atrial thrombus formation in dogs with atrial fibrillation is much less frequent compared to people is unknown 15 . A study of dogs with atrial fibrillation found no differences in various blood test results before and after electrical cardioversion, but coagulation parameters were not determined 16 . A possible explanation for the absence of thrombus formation after electrical cardioversion in dogs is that electrical cardioversion is a much less frequently performed procedure in dogs compared to humans and, even when it is performed, postcardioversion echocardiography is not routinely performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why atrial thrombus formation in dogs with atrial fibrillation is much less frequent compared to people is unknown 15 . A study of dogs with atrial fibrillation found no differences in various blood test results before and after electrical cardioversion, but coagulation parameters were not determined 16 . A possible explanation for the absence of thrombus formation after electrical cardioversion in dogs is that electrical cardioversion is a much less frequently performed procedure in dogs compared to humans and, even when it is performed, postcardioversion echocardiography is not routinely performed.…”
Section: Discussionmentioning
confidence: 99%
“… 15 A study of dogs with atrial fibrillation found no differences in various blood test results before and after electrical cardioversion, but coagulation parameters were not determined. 16 A possible explanation for the absence of thrombus formation after electrical cardioversion in dogs is that electrical cardioversion is a much less frequently performed procedure in dogs compared to humans and, even when it is performed, postcardioversion echocardiography is not routinely performed. Furthermore, most dogs develop atrial fibrillation secondary to structural heart disease, with severe mitral valve insufficiency being the predominant structural lesion, which may limit blood stasis, lessening thrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed this information refers to the action of high voltage electrical energy, much higher than EC, to restore Afb. Moreover, Noszczyk-Nowak et al [12] suggested that low voltage EC in dogs did not affect red blood cells either clinically or statistically after the successful restoration of Afb. A limitation of their study was that blood sampling was done immediately after the shock, so the EC's effects might differ after a more extended period.…”
Section: On Admission His Vital Signs Werementioning
confidence: 99%